Perbedaan Posisi Miring Ke Kiri Dan Posisi Setengah Duduk Terhadap Waktu Kala II Pada Ibu Multipara Di RSUD Idaman Banjarbaru - Fakhriyah Fakhriyah; Siska Puji Astuti (Jurnal Kesehatan Indonesia, 2017)
Maternal Mortality Rate in Indonesia still high, it was 359/100.000 live birth. The most common is caused by prolonged labor (37%) and asphyxia neonatorum (35,9%). The left lateral position usually used if semi fowler position was not work to get childbirth. The second stage time are very important for fetus condition. This study aim to analyze the differences of lateral and semi fowler position toward second stage of labor time among multiparity maternal in RSUD Idaman Banjarbaru. Design using analytical with cohort approach. Subjects were 30 normal multIparity maternal on second stage phase on Desember 2016 to March 2017. The result were lateral position mean was 12,40 minutes and semi fowler position mean was 22,47 minutes. Independent T test show there is difference of lateral and semi fowler position toward second stage of labor time. Based on these result, a midwife supposed to implement lateral position as best labor position instead semi fowler